2010
DOI: 10.1111/j.1365-3083.2010.02452.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA Vaccine Constructs Expressing Mycobacterium tuberculosis-Specific Genes Induce Immune Responses

Abstract: RD1 PE35, PPE68, EsxA, EsxB and RD9 EsxV genes are present in Mycobacterium tuberculosis genome but deleted in Mycobacterium bovis BCG. The aim of this study was to clone these genes into DNA vaccine vectors capable of expressing them in eukaryotic cells as fusion proteins, fused with immunostimulatory signal peptides of human interleukin‐2 (hIL‐2) and tissue plasminogen activator (tPA), and evaluate the recombinant DNA vaccine constructs for induction of antigen‐specific cellular immune responses in mice. DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 37 publications
0
48
0
Order By: Relevance
“…Groups of 6-8 week old BALB/c mice (five mice in each group) were immunized intramuscularly with three doses of purified parent or recombinant plasmid DNA, each dose containing 100 μg of DNA, and given 3 weeks apart. After 3 weeks of the third immunization, spleen cells were isolated from each immunized mouse for cellular immune responses using antigen-induced proliferation as an indicator (Hanif et al, 2010c). The results demonstrated that spleen cells of mice un-immunized or immunized with the parent plasmids did not show positive antigen-induced proliferation responses to any of the antigens corresponding to the cloned genes (Hanif et al, 2010c).…”
Section: Cloning Expression and Immunogenicity Of Rd Genes In Dna Vamentioning
confidence: 99%
See 2 more Smart Citations
“…Groups of 6-8 week old BALB/c mice (five mice in each group) were immunized intramuscularly with three doses of purified parent or recombinant plasmid DNA, each dose containing 100 μg of DNA, and given 3 weeks apart. After 3 weeks of the third immunization, spleen cells were isolated from each immunized mouse for cellular immune responses using antigen-induced proliferation as an indicator (Hanif et al, 2010c). The results demonstrated that spleen cells of mice un-immunized or immunized with the parent plasmids did not show positive antigen-induced proliferation responses to any of the antigens corresponding to the cloned genes (Hanif et al, 2010c).…”
Section: Cloning Expression and Immunogenicity Of Rd Genes In Dna Vamentioning
confidence: 99%
“…2, 3). In this way, a total of 10 recombinant DNA plasmids (five for each vector) were constructed (Hanif et al, 2010c). To study the expression and immunogenicity of the RD1 and RD9 proteins cloned in the recombinant vaccine constructs of pUMVC6 and pUMVC7, immunization studies were performed in mice.…”
Section: Cloning Expression and Immunogenicity Of Rd Genes In Dna Vamentioning
confidence: 99%
See 1 more Smart Citation
“…It is relatively simple to clone and is a purified DNA with no need for a synthetic protein in vitro, and can sustain long-term immune efficacy (5). The recombinant DNA vaccine is also relatively cost-effective and convenient to transport and preserve, thus it is a promising approach for the vaccine development.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, DNA vaccine has gained more attention with greater development since it maintains a long immune response and is safe as a recombinant subunit vaccine. It is effective as a live attenuated vaccine in systemic immune response, with easier cloning of DNA molecule and no requirement of protein synthesis's in vitro, extraction and purification (Hanif et al 2010). The MTB hot shock protein 65 (heat shock protein 65, Hsp65), one of earliest MTB antigen studied, may have the intense protection immune response in the animal in vivo to MTB's infection (Yoshida et al 2006;Sechi et al 2006;Okada et al 2007).…”
Section: Introductionmentioning
confidence: 99%